Impact of Post-Exercise Fructose-Maltodextrin Ingestion on Subsequent Endurance Performance - Podlogar, Tim; Wallis, Gareth A. (Frontiers in Nutrition, 2020)
Background: Current sports nutrition guidelines recommend athletes ingest carbohydrates at 1.0-1.2 g∙kg-1∙h-1 to optimise repletion of muscle glycogen during short-term recovery from endurance exercise. However they do not provide specific advice on monosaccharides (e.g. fructose or glucose) other than to ingest carbohydrates of moderate to high glycaemic index. Recent evidence suggests that combined ingestion of fructose and glucose in recovery leads to enhanced liver glycogen synthesis and that this translates into improvement of subsequent endurance capacity. Purpose: The purpose of the present study was to investigate whether consuming a combination of fructose and glucose as opposed to glucose alone during short-term recovery (i.e. 4 hours) from exhaustive exercise would also improve subsequent pre-loaded cycle time trial (TT) performance. Methods: 8 participants (7 men, 1 woman; V̇O2peak: 56.8±5.0 mLO2∙min-1∙kg-1; Wmax: 352±41W) participated in this randomised double-blind study. Each experimental session involved a glycogen reducing exercise bout in the morning, a 4-h recovery period and 1-h of steady state (SS) exercise at 50% Wmax followed by a ~40-min simulated TT. During recovery carbohydrates were ingested at a rate of 1.2 g-1∙h-1 in the form of fructose and maltodextrin (FRU+MD) or dextrose and maltodextrin (GLU+MD) (both in 1:1.5 ratio). Substrate oxidation rates, including ingested carbohydrate oxidation, were determined during the steady state (SS). Blood samples were collected during recovery, during the SS exercise and at the end of the TT for determination of glucose and lactate concentrations. Results: There were no differences in TT performance (37.41±3.45 (GLU+MD); 37.96±5.20 minutes (FRU+MD), p=0.547). During the first 45-min of SS oxidation of ingested carbohydrates was greater in FRU+MD (1.86±0.41 g-1∙min-1 and 1.51±0.37 g-1∙min-1 for FRU+MD and GLU+MD, respectively; time x condition interaction p=0.003) and there was a trend towards higher overall carbohydrate oxidation rates in FRU+MD (2.50±0.36 g-1∙min-1 and 2.31±0.37 g-1∙min-1 for FRU+MD and GLU+MD, respectively; p=0.08). However, at 60-min of SS, differences in substrate oxidation disappeared. Conclusion: Ingestion of combined fructose and glucose compared to glucose only during recovery from an exhaustive exercise bout increased the ingested carbohydrate oxidation rate during subsequent exercise. Under the conditions studied, subsequent TT performance was not improved with fructose-glucose.